Effect of Fishing Season and Size on the Physicochemical and Microbiological Characteristics of Salted Sardines (Sardina pilchardus) - Charifa Aoua; Bouchra Yacoubi; Abderrahmane Zekhnini (International Journal of Food Science)
Salting is the preferred method used by manufacturers to preserve the quality of fish. The aim of this study was to investigate the effect of size and fishing season on the physicochemical and microbiological characteristics of sardines. Two batches of sardines, caught, in winter and summer, were sorted according to size, salted, matured, and stored at 18°C. A control batch, consisting of sardines from the summer batch, was also prepared without subcutaneous fat. Various physicochemical and microbiological parameters were monitored during 12 weeks of maturation. The recorded values showed a decrease in pH, moisture content, and water activity (a measure of the water available for biological and chemical processes), while salt concentration increased. When comparing samples, the lowest values for histamine (94.3 and 48.3 mg/kg) and lipids (9.3 and 8.2%) were observed in the large and small sardines of the winter batch, respectively. In the summer batch, higher values were recorded for histamine (847.3 and 127.9 mg/kg) and lipids (14.5 and 8.6%) in the large and small sardines. Furthermore, the removal of fat in control of the summer batch resulted in lower histamine accumulation compared to the batch with fat. The microbiological parameters showed a decrease in the number of nonhalophile bacteria, while the number of halophile bacteria increased. This study showed a strong correlation between three important factors, fishing season, fish size, and histamine content, which can contribute to the successful salting of sardines and ensure the wholesomeness of the final product.